A taxonomic database for the pinewood nematode Bursaphelenchus xylophilus, and other Bursaphelenchus species - VIEIRA, Paulo (2013)
The main objective of this project is to develop an information database with the inclusion of text (research articles, keys, bibliography, etc.), images (jpeg files), video clips (mpeg files), in order to collect in one physical format (CD-ROM) all relevant information related to the taxonomy of pine wood nematode (PWN), Bursaphelenchus xylophilus, as well as other Bursaphelenchus species. Initially, all major research papers will be scanned in ‘pdf’ format. All available images of quality and importance to the subject will also be scanned from either journals, bulletins, reports, or obtained privately from colleagues’ image collections. In certain cases, image quality (brightness, contrast, colour) may be enhanced with Adobe Photoshop. Short video clips will be compressed to ‘mpeg’ format for inclusion in the CD-ROM. An updated and broad bibliography will be included, as well as an intuitive taxonomic key, based on classical dicotomous keys but with a better and more intuitive presentation. Pre-existing images will be used in most cases; however, nematode specimens may need to be observed and photographed (jpeg image) in the lab. All the incorporated elements will be interlinked for ease of search from text to image to video. The total collection of images may be viewed individually using ‘Extensis Portfolio’. The final product will be PC and Mac compatible. Future editions/updates will be developed. Ultimately, researchers, technicians and political decision-makers will have at their disposal a practical and readily available source of information on this extremely important pest and pathogen. Colleagues working with PWN are encouraged to provide materials for this task.